LOS MAPAS CONCEPTUALES EN EL PROCESO DE ENSEÑANZA - APRENDIZAJE DE LA BIOLOGÍA 2 - Armiñana-García, Rafael (2020)
The work consists of the design, elaboration and proposal of a concept map system with the use of Information and Communication Technologies (ICT) to contribute to the learning of concepts in the teaching-learning process of Biology 2 (Zoology), in secondary education. The research uses various theoretical and empirical methods in its dialectical interrelation, which allows one to verify existing gaps in the use and elaboration of concept maps in the teaching-learning process of this subject. A total of 15 concept maps was built in electronic format covering all the units of the program, based on the concept of animal, and all taxonomic groups from the poriferans to the mammals. The concept maps were introduced in the teaching-learning process of Biology 2 from the 2018-2019 academic years. The proposed system, until its implementation, was evaluated by different specialists who considered it relevant, as well as the criteria offered by teachers and students once the instruments such as surveys and interviews were applied, respectively. Key words: teaching – concepts – conceptual maps – learning process – Information and Communication Technologies